Ideologi Sosial Dalam Kesenian Tradisional Angklung Sered: Dari Alat Perjuangan Hingga Sebagai Sarana Hiburan Masyarakat - Agus Ahmad Wakih; Juju Masunah; Tati Narawati; Cece Rakhmat (LP2M ISBI Bandung, 2023)
ABSTRACT For 350 years, Indonesia was under the rule of foreign countries before gaining independence in 1945. This colonization had a significant impact on the social, cultural, economic, and political aspects of Indonesian society. The people expressed their resistance through traditional performing arts, such as angklung sered in Balandongan, Tasikmalaya, West Java. This art form served as a tool of struggle against the colonizers. The objective of this research is to discover the values of social ideology embedded in angklung sered within the community of Balandongan. The research methodology employed semiotic analysis, focusing on the text and context of the angklung sered performances. Text analysis emphasizes the musical instrument used in the performance, while contextual analysis examines the artistic function of angklung sered before and after independence. The research data was obtained through interviews and documentary studies. The findings reveal that angklung sered served as a symbol of resistance before independence, while after independence, the emphasis shifted towards the aesthetics of the performance. Angklung sered also became a social ideology for the community, reflected in its meanings and symbols, serving as the foundation of their beliefs in everyday life. Keywords: Social Ideology, Culture, Traditional Art, Angklung Sered, Traditional Performing Arts ABSTRAK Selama 350 tahun, Indonesia dikuasai oleh negara-negara asing sebelum merdeka pada tahun 1945. Penjajahan ini berdampak besar pada sosial, budaya, ekonomi, dan politik bangsa Indonesia. Masyarakat menunjukkan perlawanan melalui seni pertunjukan tradisional seperti angklung sered di Balandongan, Tasikmalaya, Jawa Barat. Seni ini dijadikan sebagai alat perjuangan melawan penjajah. Penelitian ini bertujuan menemukan nilai-nilai ideologi sosial masyarakat dalam angklung sered di Balandongan. Metode penelitian menggunakan analisis semiotika, fokus pada teks dan konteks pertunjukan angklung sered. Analisis teks berfokus pada alat musik angklung yang digunakan, sedangkan analisis konteks memeriksa fungsi kesenian ini sebelum dan setelah kemerdekaan. Data penelitian diperoleh melalui wawancara dan studi dokumentasi. Hasil penelitian menunjukkan angklung sered sebelum kemerdekaan menjadi simbol perjuangan, sementara setelahnya lebih menekankan estetika pertunjukan. Angklung sered juga menjadi ideologi sosial masyarakat, tercermin dalam makna dan simbolnya yang menjadi dasar keyakinan dalam kehidupan sehari-hari. Kata kunci: Ideologi Sosial, Budaya, Kesenian Tradisional, Angklung Sered, Seni Pertunjukan Tradisional